Pilot study: Impact of school director-led workplace professional development training for in-service teachers - Oluwaseyi Olubunmi Sodiya; Samira Hajiyeva (Journal of Education and Learning (EduLearn), 2022)
Teacher’s attitudes and strategies can be influenced by workplace professional learning, which in turn affects student engagement and learning. Although educators are accountable for their professional development, the school must be learning-centered and able to provide resources for all members of the institution to improve their teaching and learning skills for the overall development of the school. The project's goal was to perform a pilot intervention study on the impact of school director-led workplace professional development for in-service teachers to provide evidence and recommendations on the impact of school director-led workplace professional development training for teachers. The intervention study on school director-led workplace professional development training for teachers on formative assessment indicates that there were significant changes in teachers’ understanding and use of formative assessment. The result found that there is statistical difference between the teacher’s pre- and post- intervention survey response on formative assessment workplace professional development training. The evidence stands as a recommendation for school directors, teachers, the ministry of education and other stakeholders for quality teaching and whole school development.